Phenotypic speciation of enterococci with special reference to prevalence, virulence and antimicrobial resistance - Manavalan, Jayavarthinni; Kannaiyan, Kavitha; Velayutham, Abarna; Vadivel, Sindhanai; Kuthalaramalingam, Sethumadhavan (International Journal of Research in Medical Sciences, 2017)
Background: Now considered as one of the most important Nosocomial pathogen, enterococci have been found to possess virulence factors like biofilm formation and are increasingly exhibiting antimicrobial resistance in India. This study was undertaken to estimate the prevalence of enterococci from various clinical samples simultaneously correlating their virulence property and antimicrobial resistance, in addition to speciation. Methods: A total of 126 enterococcal isolates from various clinical samples were included and processed according to standard protocols and speciation was based on Facklam and Collins conventional method. Virulence determinants like hemolysin, gelatinase and biofilm formation were assessed by phenotypic tests. Antibacterial susceptibility pattern was determined by Kirby Bauer disc diffusion method with recommended drugs including high level aminoglycoside resistance. Minimum inhibitory concentration (MIC) for vancomycin was done by E-test. Results: Out of 1746 clinical samples, enterococci accounted for 7.22%. They consisted of E. faecium 52.38%, E. faecalis 32.54%, and E. avium 15.08% isolated from urine 8.26%, pus 8.44%, blood 0.56% and body fluids 1.28%. Study on virulence factors revealed that 19.84% strains produced gelatinase, 18.25% produced hemolysin and 73.81% produced biofilm. High level resistance to gentamycin and streptomycin were 4.76% and 5.56% respectively. Vancomycin resistance was 3.17%. Conclusions: This study indicates the change in epidemiology of enterococcal infections from E. faecalis to E. faecium and low prevalence of vancomycin resistant enterococcus (VRE) in our region. To maintain the low level of resistance, improvement of antibiotic policies and hospital infection control is essential.